Metabolic syndrome and its associated factors in patients with severe mental illness in Malaysia - Z., Nur Sabrina; Gan, W. Y.; Ang, J. K.; I., Siti Irma Fadhilah; Chan, Y. M. (Community Health Society Malaysia, 2018)
Background: Mental illness is a huge public health issue. Patients with severe mental illness (SMI) are at risk of developing metabolic syndrome (MetS). Therefore, this cross-sectional study aimed to determine the associations between personal, clinical and lifestyle factors with MetS in patients with SMI. Materials and Methods: 151 patients attending psychiatric outpatient clinics in two government hospitals in Klang Valley participated in this study. The Mini International Neuropsychiatric Interview (MINI) was used to diagnose patients with SMI by a psychiatrist. MetS was defined based on the 2009 Joint Interim Statement (JIS) criteria. Information needed on socio-demographic background, clinical characteristics (types and duration of illness and medication), lifestyle factors (physical activity level, smoking behaviour and alcohol consumption) were collected through a face-to-face interview. Body weight, height, waist circumference, percentage of body fat and blood pressure were measured by the researchers. Blood test results were obtained from the medical records. Result: Nearly half of the respondents (48.3%) had MetS, in which it was higher among males (48.5%), married respondents (61.5%), older age group (66.7%) and schizophrenic patients (50.7%). Overweight (AOR=3.64, 95% CI=1.55-8.58) and obese (AOR=15.06, 95% CI=5.27-43.09) patients were more likely to develop MetS. Moreover, middle-aged and older patients were about 3 times (AOR=3.31, 95% CI=1.38-7.94) and 6 times (AOR=5.65, 95% CI=1.62-19.73), respectively, more likely to develop MetS compared to younger patients. Conclusion: This study demonstrated high prevalence of MetS among patients with SMI. It also highlighted the need of regular assessment of BMI among patients with SMI to prevent MetS.